Verteporfin inhibits growth of human glioma in vitro without light activation - Ahmad Al-Moujahed (Nature Portfolio, 2017)
Abstract Verteporfin (VP), a light-activated drug used in photodynamic therapy for the treatment of choroidal neovascular membranes, has also been shown to be an effective inhibitor of malignant cells. Recently, studies have demonstrated that, even without photo-activation, VP may still inhibit certain tumor cell lines, including ovarian cancer, hepatocarcinoma and retinoblastoma, through the inhibition of the YAP-TEAD complex. In this study, we examined the effects of VP without light activation on human glioma cell lines (LN229 and SNB19). Through western blot analysis, we identified that human glioma cells that were exposed to VP without light activation demonstrated a downregulation of YAP-TEAD-associated downstream signaling molecules, including c-myc, axl, CTGF, cyr61 and survivin and upregulation of the tumor growth inhibitor molecule p38 MAPK. In addition, we observed that expression of VEGFA and the pluripotent marker Oct-4 were also decreased. Verteporfin did not alter the Akt survival pathway or the mTor pathway but there was a modest increase in LC3-IIB, a marker of autophagosome biogenesis. This study suggests that verteporfin should be further explored as an adjuvant therapy for the treatment of glioblastoma.